2013
DOI: 10.1049/iet-rpg.2012.0135
|View full text |Cite
|
Sign up to set email alerts
|

Optimisation tools for large permanent magnet generators for direct drive wind turbines

Abstract: As wind turbines increase in power output, their size and mass grows as well. The development of offshore wind farms demands higher reliability to minimise the maintenance cost. Direct drive electrical generators offer a reliable alternative to conventional doubly fed induction generator machines since they omit the gearbox from the drive train. A fundamental issue for these generators is their large size which makes them difficult to manufacture, transfer and assemble. This study will investigate an analytica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 15 publications
0
27
0
Order By: Relevance
“…where FCR represents the fixed charge rate given in Table I, ICC is the initial capital cost of the turbine and AOM is the annual operation and maintenance cost given in Table I (assumed to be fixed for different machine design). The initial capital cost can be calculated as, = gact + gstr + tower + sf + fan + hex + rt (13) where Cgact is the generator active materials cost, Cgstr is the generator structural materials cost, Ctower is the tower cost, Csf is the substructure and foundation cost, Chex is the cost of heat exchanger and Crt is the rest of the turbine cost given in Table I.…”
Section: ) Objective Functionsmentioning
confidence: 99%
See 1 more Smart Citation
“…where FCR represents the fixed charge rate given in Table I, ICC is the initial capital cost of the turbine and AOM is the annual operation and maintenance cost given in Table I (assumed to be fixed for different machine design). The initial capital cost can be calculated as, = gact + gstr + tower + sf + fan + hex + rt (13) where Cgact is the generator active materials cost, Cgstr is the generator structural materials cost, Ctower is the tower cost, Csf is the substructure and foundation cost, Chex is the cost of heat exchanger and Crt is the rest of the turbine cost given in Table I.…”
Section: ) Objective Functionsmentioning
confidence: 99%
“…Different authors have approached different optimization methods with different objective functions to minimize the generator cost of active materials, cost of structural materials, losses, masses and maximize the efficiency and annual energy productions [5], [10][11][12][13]. A hybrid algorithm combining T Genetic Algorithms (GA) with Pattern Search (PS) is used in [9].…”
Section: Introductionmentioning
confidence: 99%
“…The model was constrained at the shaft and a mesh size of 100mm was utilised [5]. The structures were analysed for mode 1 assuming a deformation of = 0.0027m and = 0.0015m in a 5mm air-gap.…”
Section: Structural Stiffness Finite Element Analysismentioning
confidence: 99%
“…Bazzo et al outlined some objective functions to minimize costs and maximize efficiency which included minimizing active and structural materials cost and minimizing cost of losses to get maximum return of investment [9]. Zavvos et al offered an analytical tool that minimizes the generators mass or cost by optimizing both the electromagnetic and structural design at the same time [10]. Wu et al also outlined the optimization of generator rotor structure for minimum generator mass where deflections were constrained [11].…”
Section: Introductionmentioning
confidence: 99%
“…With this technique a global search is carried out first using the GA and an intermediate set of solutions are found after a few generations. These solutions are used as initial parameters for Most of the generator models in [4][5][6][7][8][9][10][11] focus on the active material and losses but do not consider the generator structure in detail. McDonald showed that the structural mass of a 5 MW permanent magnet direct drive generator can be more than 80% of its total mass [16].…”
Section: Introductionmentioning
confidence: 99%